Attractiveness of Forest Research Institute of Malaysia canopy walkway as a nature-based tourism product - Ramlan, Mohd Aswad (2012)
FRIM Canopy Walkway is one of the main attractions for visitors at the Forest Research Institute Malaysia (FRIM). Since its opening, the walkway has recorded visitations from all over the world thus bringing good revenues to the management. As a new niche, canopy tourism is still in its initial stages and is currently lack in research. Hence, information regarding FRIM canopy tourism is essential for the managers in enabling them to assist and better manage the canopy walkway. Due to this, a study was conducted to assess visitors’ perception towards the attractiveness of FRIM Canopy Walkway as a nature-based tourism product. The study was also carried out to draw visitors’ information associated with the socio-demographic backgrounds, travel characteristics as well as determining the discriminating variables, which can best differentiate between users and non-users of the walkway. Questionnaires were distributed to the visitors between March and June 2010 whereby a total of 736 surveys were completed.The conceptual framework in this study was constructed based on the Fishbein’s Multiattribute model. The results from the study indicate that the model provides beneficial means for the evaluation on multiple attributes as well as measurement on the attractiveness of FRIM canopy tourism. From this approach, it was revealed that the attractiveness factor of FRIM Canopy Walkway is the ‘view from the walkway’. Through the Importance-Performance Analysis (IPA), it was also revealed that the attribute ‘view from the walkway’ as the strength of FRIM Canopy Walkway, whereas the ‘numbers of interpretive signage’ as the weakest attribute. However, non-users are found to deem ‘existence of entrance fee’ as not important while the users ranked ‘usage of guides at the walkway’ as low. The results of the study further revealed that the function characterized as ‘time spent with quality service facility’ is regarded as the best predictors in discriminating the user and the non-user groups. In conclusion, this study is significant in providing an in-depth insight on the attractiveness of FRIM Canopy Walkway as a nature-based tourism product. Hence, the results from this study would not only be valuable to the managers and stakeholders of the facility, but also served to show the importance of conservation of the resources. Idyllically, it is hoped that the findings from this study will be used as a preliminary guideline for the management of FRIM Canopy Walkway as well as for the management of Malaysian canopy tourism in general.